2018
DOI: 10.1080/1177083x.2018.1452763
|View full text |Cite
|
Sign up to set email alerts
|

Using environmental imperatives to reduce meat consumption: perspectives from New Zealand

Abstract: Sustainable food consumption is an important issue globally, that will intensify if current projections of population growth, urbanisation and the growing 'middle-classes' in developing countries continues. Reducing meat consumption is one approach that can help with food sustainability and security, while helping to address the problematic environmental outcomes associated with agricultural productionassuming that a reduction in meat consumption will at some point be reflected in production practices. Current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…As we observed in our previous review, partly due to the perception of cultured meat as unnatural, it is common for consumers to have intuitive questions about its safety [12,53,60]. More recent research builds on this theme [22,35,36]. In particular, focus group and interview participants expressed anxiety about the uncertainty on the long-term health effects of cultured meat [35], while Tucker [36] notes that such fears appear to be extensions of concerns about unnaturalness.…”
Section: Safety Concernsmentioning
confidence: 86%
See 4 more Smart Citations
“…As we observed in our previous review, partly due to the perception of cultured meat as unnatural, it is common for consumers to have intuitive questions about its safety [12,53,60]. More recent research builds on this theme [22,35,36]. In particular, focus group and interview participants expressed anxiety about the uncertainty on the long-term health effects of cultured meat [35], while Tucker [36] notes that such fears appear to be extensions of concerns about unnaturalness.…”
Section: Safety Concernsmentioning
confidence: 86%
“…Recent studies further fortify this observation [21]. Tucker [36] reports focus group participants commenting that a lack of knowledge about cultured meat was a barrier for them, whilst Weinrich et al [31] identified prior knowledge about cultured meat as being conducive to positive views about its morality, and found this to be the strongest driver of acceptance. A low overall awareness of cultured meat [30], combined with research which again highlights the importance of food neophobia in cultured meat rejection, [21,23,32] means that there is plenty of room for educating the public about cultured meat, normalizing the concept, and making it more well-known.…”
Section: Demographic Predictorsmentioning
confidence: 99%
See 3 more Smart Citations